Fungal Communities Resist Recovery in Sand Mine Restoration - Hart, Miranda; Gorzelak, Monika A.; McAmmond, Breanne M.; Van Hamme, Jonathan D.; Stevens, Jason; Abbott, Lynette; Whiteley, Andrew S.; Nevill, Paul (Frontiers in Forests and Global Change, 2019)
The restoration of vegetation post mining is particularly challenging in extreme conditions such as Mediterranean systems where soil moisture is limiting, soil temperature fluctuates dramatically, and soil carbon is very low. In such systems, soil microbial communities may play an important role in attenuating extreme conditions. Thus, vegetation establishment on such sites may be curtailed by depauperate soil communities. Soil fungal communities, in particular, are essential for nutrient turn over but we know very little about how these communities respond to mining and post mining restoration. Fungi may be significantly affected by restoration practises. For example, the inclusion of deeper soil profiles (i.e. “overburden”) into restoration events is rare, but may expedite fungal community development. We studied a successional gradient of sand mine restoration in a former Banksia woodland in SW Australia to determine whether soil fungal communities recovered after 13 years. We also asked whether the inclusion of overburden into restoration sites improved soil fungal community development. Overall, fungal communities did not return to a pre-disturbance state by 13 years, nor did the inclusion of overburden affect their trajectory. Longer term studies are need to determine when, if ever, fungal communities are restored, and what effect this has nascent vegetation.